Endoscopic transorbital avenue to the skull base: Four-step conceptual analysis of the anatomic journey - Guizzardi, Giulia; Di Somma, Alberto; de Notaris, Matteo; Corrivetti, Francesco; Sánchez, Juan Carlos; Alobid, Isam; Ferres, Abel; Roldan, Pedro; Reyes, Luis; Enseñat, Joaquim; Prats-Galino, Alberto (Frontiers in Oncology, 2022)
endoscopic transorbital, endoscopic skull base surgery, endoscopic transorbital anatomy, skull base anatomy, surgical planning